Atypical presentation of Monkeypox virus infection - Lionel Fourcade; Jilliana Monnier; Emilie Bourgea; Caroline Gaudy‐Marqueste; Marie‐Aleth Richard (Wiley, 2023)
Abstract A 69‐year‐old man was referred for a necrotic lesion on the nose suggestive of bacterial infection. The patient had a HIV‐positive status with normal CD4+ T‐cell count and undetectable viral load. Despite antibiotic treatment, the lesion expanded, and vesiculopustular lesions appeared on the legs and hands. Monkeypox infection was diagnosed by polymerase chain reaction of swabs obtained from lesions on the hands and nose. This unusual presentation, suggestive of bacterial cellulitis of the face, highlights the importance of extra‐genital presentations of Monkeypox infection.